(untitled) (Research, Society and Development, 2021)
This research aims to evaluate the quality management and its tools in order to understand its applicability in food industries of animal origin. The methodology used for the development of this work was based on a qualitative approach with bibliographic survey in databases of the Ministry of Agriculture, Cattle and Supplying, Scielo, Pubmed and Google Scholar through agreement between terms. Among the tools available for the food industries of animal origin, the self-control programs established by Circular n. 175, of May 16, 2005 and Internal Standard n. 01, of March 8, 2017, both from the Ministry of Agriculture, Cattle and Supplying (MAPA), are procedures that meet the safety and food security conditions required by legislation, as they are based on systematic continuous inspections of all factors that may interfere in some way in the quality of products exposed to the population’s consumption. In this way, the application and understanding of quality management and tools such as self-control programs align up with the results presented, since self-control programs ensure the condition of food security through its implementation, which is defined and controlled by quality management system, which ensures that the inspected elements will be identified and controlled in the process, with this, added to their beneficial use, since it converges with the recommended legislation, brings validation, safety and product quality, and consequently, achieves credibility when competing with foreign markets and support with the final consumer.